The Advent of Europe’s Industrial Heritage as a Field of Research: The contribution of Maurice Daumas through the CNAM Survey - Belot, Robert (Ethnologies, 2020)
Maurice Daumas (1910-1984) was a founder, but whose name is now forgotten. He was a curator at the Conservatoire national des Arts & Métiers (Paris), then holder of the first Chair in the history of techniques, and he directed the monumental Histoire générale des techniques. It was him who brought industrial heritage into the French academic field by founding the journal L’Archéologie industrielle en France and by publishing in 1980 a book with the same title. In this book, Daumas evokes in particular the glorious timesof industrial history in the Saint-Étienne region. Following the recent discovery of the archives of the national survey that he conducted over several years to document his book, I propose to examine the way in which he approached the industrial heritage of Saint-Étienne, the first French industrial city for a long time, by updating the methodology he used and the local networks on which it relied. In sum, this contribution is about the birth of a field of research in France and in Europe: industrial archeology.